NÃVEIS DE FERTILIDADE DE SOLO NAS MICRORREGIÃ•ES HOMOGÃŠNEAS DO ESTADO DA PARAÃBA - Tejada, H. R.; Rocha Filho, J. V. de C.; Alcoforado, C. B.; Costa, G. T.P. da; Baracho, M. das D. M. (REVISTA DE AGRICULTURA, 2015)
NÃVEIS DE FERTILIDADE DE SOLO NAS MICRORREGIÃ•ES HOMOGÃŠNEAS DO ESTADO DA PARAÃBA